Indigenizing Engineering education in Canada: critically considered. Issue 7 (17th November 2021) - Seniuk Cicek, Jillian; Steele, Alan; Gauthier, Sarah; Adobea Mante, Afua; Wolf, Pamela; Robinson, Mary; Mattucci, Stephen
ABSTRACT: This article critically considers the work being done to bring Indigenous Peoples, Knowledges, and perspectives into the dominant structures of engineering education in Canada. We use Gaudry and Lorenz's (2018. "Indigenization as Inclusion, Reconciliation, and Decolonization: Navigating the Different Visions for Indigenizing the Canadian Academy." AlterNative: An International Journal of Indigenous PeoplesAlterNative 14 (3): 218–227. doi:10.1177/1177180118785382) spectrum of Indigenization to evaluate self-reported contributions from 25 engineering programs and four engineering organizations. Findings show much of the work being done in Canada is in Indigenous Inclusion and Reconciliation Indigenization, with some Decolonial Indigenization. Efforts in reconciliation and decolonization are seen predominantly in integrated, grassroots initiatives, with institutional initiatives found largely in inclusion. We submit that a diversified strategy and decolonized policies are needed to achieve Decolonial Indigenization. The intention of this work is to create an ethical space where Indigenous and non-Indigenous engineering educators can listen to and learn from one another. Guided by Etuaptmumk ( Two-Eyed Seeing ), we can advance Indigenous ways of knowing, being, and doing in engineering education in Canada and around the world.